Pulmonary-renal syndrome associated with antineutrophil cytoplasmic antibodies - Didenko, Irina (2009)
The pulmonary-renal syndrome is defined by the association of alveolar haemorrhage and rapidly progressive glomerulonephritis, resulting from several diseases and frequently associated with serum positivity for antineutrophil cytoplasmic antibodies (ANCA). The most common illness presenting as pulmonary-renal syndrome is systemic vasculitis. Wegener´s granulomatosis, microscopis polyangiitis and Churg-Strauss syndrome are described as small vessel vasculitides strongly associated with ANCA. The diagnosis of ANCA-associated vasculitis is made on the basis of clinical findings, by biopsy of a relevant involved organ and the presence of ANCA. However, the application of ANCA testing as a clinical diagnostic tool is still regarded as controversial. Accurate understanding of the key pathogenic points of ANCA-associated vasculitis can undoubtedly provide a more rational therapeutic approach.